FORMULASI HYBRID MODEL PEMBELAJARAN VIRTUAL DALAM MASA TRANSISI MENUJU NEW NORMAL PANDEMI COVID 19 - Rayung Wulan; Suranto Saputra; Yogi Bachtiar (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
AbstractThe 19 covid pandemic have fully come more than a year turning the method of learning throughout the world , especially in indonesia in urban village sub district junior high school virtual learning model when normal running with the new protocol strictly adhere to all . Hybrid learning model applied SMPN 101 west Jakarta using formulation hybrid model , the merger of the kind of classroom virtual and face to face .Formulation hybrid learning model is applied as a form of transition toward new normal by combining learning model virtually and face to face. The goal of the learning cannot be done virtually, with learning activities ( face to face face to face classroom ) method applied can help learning cannot dilalukan virtually including learning practice and counseling children be measured by way of looking at the gesture body of children. Students remember pandemic covid 19 are still continue to mutate and the program continued, learning formulation hybrid model excellent SMPN 101  applied in west Jakarta.